Anticancer Assay of Methanol Extract of Gracilaria salicornia Originating from the Hari Islands, Southeast Sulawesi, Against MCF-7 Cancer Cells - Sernita, Sernita; Taba, Paulina; Sahidin, I; Soekamto, Nunuk Hariani (PSPP JOURNALS, 2025)
Marine macroalgae represent a promising but underexplored resource for anticancer drug discovery due to their diverse repertoire of bioactive secondary metabolites. Gracilaria salicornia, a red alga found abundantly in the waters surrounding the Hari Islands, Southeast Sulawesi, has not been previously studied for its cytotoxic potential. This study aimed to evaluate the phytochemical composition and anticancer activity of methanol extract from G. salicornia against MCF-7 human breast cancer cells. The algae were extracted using a gradient solvent system, with methanol selected for further testing due to its polarity and broad extraction capacity. Phytochemical screening revealed the presence of alkaloids, phenolics, and steroids/terpenoids—classes of compounds known for their cytotoxic, pro-apoptotic, and redox-modulatory properties. General toxicity was assessed using the Brine Shrimp Lethality Test (BSLT), with the extract demonstrating moderate toxicity (LC₅₀ = 561.26 mg/L), indicating the presence of bioactive constituents. Cytotoxicity against MCF-7 cells was evaluated using the MTT assay, yielding an IC₅₀ value of 414.6 mg/L. Although lower than the standard chemotherapeutic agent doxorubicin (IC₅₀ = 4.1 mg/L), the observed activity supports the hypothesis that G. salicornia contains compounds with therapeutic relevance. These findings suggest that G. salicornia harbors cytotoxic agents that act through diverse mechanisms, likely involving oxidative stress and hormonal regulation. While the crude extract exhibited only moderate activity, its phytochemical richness warrants further fractionation, isolation, and mechanism-of-action studies. This study provides foundational evidence for the potential of Indonesian marine algae in cancer drug discovery and highlights the need for continued exploration of native marine biodiversity as a source of novel chemotherapeutic agents.